Sociocultural Aspects in English Phraseology: Perspectives of Study - Florentina Mena Martínez; Piedad Fernández Toledo (Miscelánea: A Journal of English and American Studies, 2003)
The permeability of phraseology with respect to the socio-cultural aspects that characterise languages is a commonly accepted fact. The relationship between phraseology and socio-cultural cues is particularly close and manifests itself in many different ways. This is why linguists have devoted their efforts to the observation of certain more or less particular issues. However, there is a lack of studies that offer a global vision of the different ways in which contact between these two realities takes place. Systematising the ubiquity of socio-cultural reality in phraseology is not a simple task, and implies the need to consider the axes around which this relationship takes place. In this article we propose a classification of the different perspectives from which the relationship between phraseology and sociocultural reality can be approached with reference to the English language.